Fine tuning of the catalytic effect of a metal-free porphyrin on the homogeneous oxygen reduction - Trojánek, Antonín; Langmaier, Jan; Šebera, Jakub; Záliš, Stanislav; Barbe, Jean-Michel; Girault, Hubert H; Samec, Zdeněk (Chemical communications (Cambridge, England), 2011)
The catalytic effect of tetraphenylporphyrin on the oxygen reduction with ferrocene in 1,2-dichloroethane can be finely tuned by varying the molar ratio of the acid to the catalyst present in the solution. The mechanism involves binding of molecular oxygen to the protonated free porphyrin base, in competition with ion pairing between the protonated base and the acid anion present.